The universities and management training - Garmany, J. W. (Statistical and Social Inquiry Society of Ireland, 1959)
The post-war years have seen a significant increase in the attention given to the problems of business management and to the devising of courses covering a wide variety of subjects but all subsumed under the general heading of management or administration and all purporting to offer useful training to those looking forward, or already in, executive positions in business. A recently published British Institute of Management conspectus lists nearly 200 such courses in the United Kingdom, most of them run by the technical colleges. In addition, many large firms have their own training programmes. The B.I.M. and its counterpart in Dublin, the Irish Management Institute, play their part by co-ordinating these activities, by stimulating interest and by disseminating thought and literature on management principles and practice.
Read before the Society, January 26 1959
Keywords: Management training; Universities; Business administration; 314.15